The Connection Between Perceived Value and Healthcare Service Quality on Revisit Intention at Siloam Hospitals with Patient Satisfaction as a Mediating Factor - Arif Laksono Utomo (Riviera Publishing, 2025)
This study examines how Healthcare Service Quality and Perceived Value affect Revisit Intention through Patient Satisfaction at Siloam Hospitals. As Indonesia's largest network yet ranking below competitors, Siloam's patient satisfaction gaps impact its market position. Understanding these relationships is crucial for improving service quality and patient retention in competitive healthcare markets. The research aims to assess the direct and indirect effects of Healthcare Service Quality and Perceived Value on Revisit Intention, focusing on the mediating role of Patient Satisfaction. The study offers insights into improving patient loyalty and service quality in hospitals like Siloam. A quantitative cross-sectional design was employed, collecting data via an online questionnaire from 313 patients at three Siloam hospitals in Jakarta. Simple random sampling was used, and data was analyzed with Partial Least Square - Structural Equation Modelling (PLS-SEM) to evaluate the relationships between Healthcare Service Quality, Perceived Value, Revisit Intention, and Patient Satisfaction. Both Healthcare Service Quality and Perceived Value positively influence Patient Satisfaction. Perceived Value directly impacts Revisit Intention, while Healthcare Service Quality affects it indirectly through Patient Satisfaction. Healthcare Service Quality alone does not directly influence Revisit Intention. The study emphasizes the importance of Healthcare Service Quality and Perceived Value in boosting Patient Satisfaction, which leads to higher Revisit Intention. For Siloam Group to strengthen patient loyalty and improve its ranking, efforts should focus on providing high-quality services and ensuring patients perceive value commensurate with costs. Enhancing communication and transparency regarding service value may further improve patient experiences and encourage repeat visits.